Building Knowledge Economies : Advanced Strategies for Development - World Bank (Washington, DC: World Bank, 2012)
Knowledge has always been an essential force in economic development. Chapter one, describes the knowledge revolution, which is leading us into a postindustrial age in which brains, not brawn, are the best means of coping with intensified competition and new challenges, including those related to human development and the global environment. In explaining the foundations and the model of knowledge economies, chapter two outlines the four knowledge economies (KE) pillars, provides elements of the benchmarking methodology, and relates KE achievements to recorded growth and competitiveness. To understand the KE process, chapter three starts with the examples of three KE champions, Finland, Ireland, and the Republic of Korea. The ensuing chapters examine and document in detail the four KE policy pillars. Chapter four on the economic and institutional regime discusses governance, regulation, finance, and trade as they bear on the KE development process. Chapter five on innovation addresses the question of support for innovators, the strengthening of research and technology infrastructure, the diffusion of basic technologies, and the promotion of specific industries. Chapter six deals with the national information and communication technology (ICT) infrastructure, addressing related applications, institutions, and regulations, as well as access to that infrastructure and the development of the skills needed to build, maintain, and use it. Chapter seven looks at primary and secondary education, higher education, and lifelong learning from a KE perspective, providing insights on the mobility of human resources and the role of diasporas. Chapter eight discusses policy agendas for selected sets of countries.